Specialized Library Design Framework: Tantra Foundation Library Case Study - Tomar, GuzmanVela (Journal of Educational Research and Policies, 2026)
A special library can be defined as a library that is not academic, public, or national, it is developed by any organisation to serve its specific goals or objectives. This kind of library provides very specialised services to its parent organisation. Because these libraries have some particular goals their development is difficult and complex. To design such libraries, one needs to craft your implicit knowledge and reflection should be on your work. Such an experience is not easy because it is not the information you read somewhere and compiled in one place. This paper tries to compile the output of almost one year which developed a small but special library in its wide and varied collection. This paper discusses the design and development of a special library and the profession of a librarian. For the first time during the internship, I understood the work of a library professional in a real sense. At the same time, I came to understand a library and its various sections, holdings, working areas, librarianship, and the real soul of a library, which is “to guide your user.” This paper describes all the steps taken to develop a special library for a non - governmental organisation in Delhi “Tantra Foundation Library (TFL)” and also discusses the experiences and challenges of a library professional. The young, enthusiastic, and curious library and information professionals will benefit from this documented knowledge.